Cold Atmospheric Plasma Conveys Selectivity Against Hepatocellular Carcinoma Cells via Triggering EGFR(Tyr1068)-Mediated Autophagy - Wang, Danjun; Zhang, Jianying; Cai, Linhan; Dai, Xiaofeng (Frontiers in Oncology, 2022)
Liver cancers remain as a global health threat given its high mortality rate. We have previously identified the selectivity of cold atmospheric plasma (CAP) against multiple types of malignant tumors and proposed it as a promising onco-therapeutic strategy. Here we investigate its role in controlling liver cancer malignancy and the driving molecular mechanism. By focusing on post translational modifications including acetylation, phosphorylation and ubiquitination, we identified the crosstalk between EGFR acetylation and EGFR(Tyr1068) phosphorylation and their collective roles in determining LC3B ubiquitination and proposed the EGFR/p-JNK/BIRC6/LC3B axis in CAP-triggered autophagy. Our study not only proposed the selectivity of CAP against liver cancer malignancy and confirmed its roles as an onco-therapeutic tool, but also opened the horizon of translating CAP into clinics towards a broader scope that includes human longevity and anti-aging.